Short Circuit Analysis on Distribution Network 20 kV Using Etap Software - Arizaldi, Afif; Salahuddin, S; Muhammad, M; Jain, Vishal; Pandey, Govinda Prashad; Watane, Manoj Jagannathrao (Journal of Renewable Energy, Electrical, and Computer Engineering, 2021)
In an electric power system, electricity is generated by the power plant and then channeled to a transmission line and then distributed to consumers, in the process of distributing electrical energy, the system does not always work in normal conditions, sometimes the system can experience disturbances such as one-phase, two-phase, and three-phase disturbances. This interference can disrupt the electrical system and can damage equipment if left unchecked, therefore it is necessary to install a protection device that can decide the interference so as not to damage other equipment when a disturbance occurs. Here the protection device used is a circuit breaker. In a fault condition, the circuit breaker must be able to separate the points of the fault so as not to damage other electrical equipment. In this case, to determine the capacity of the best protection device for the system, a short circuit fault simulation is performed. To simplify the calculation process here the author uses the help of ETAP software (Electrical Transient Analysis Program).